Fenomenologia a motyw teoretyczny i praktyczny - Wesołowska, Agnieszka (Folia Philosophica, 2018)
The deliberations presented in the article are concentrated around a thesis that the unchanging framework of Husserl’s philosophical thinking is based on the simultaneous occurrence of theoretical and practical-ethical motive. This thesis, together with considerations presented in the text, are the result of reflection on the aim and tasks of phenomenology as transcendental philosophy, philosophy understood as science striving for the consolidating of cognition and revealing findings that are relevant to one’s life. The practical-ethical motivation that accompanies deliberations of epistemological nature influences the specificity of phenomenological philosophy, phenomenological inquiries and the change of approach. Phenomenology considered in terms of theoretical and practical motives, in the rational and critical thinking, includes the relation between the sphere of cognition and the sphere of life, between the theoretical-scientific sphere and the practical-ethical one.